The Effectiveness of Duolingo Application on Vocabulary Mastery in English Language Learning of Grade 10 Students at SMK Al-Kautsar Sriwijaya (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aimed to examine the effectiveness of the Duolingo application in helping 10th-grade students at SMK Al-Kautsar Sriwijaya master English vocabulary. This research is based on the understanding that vocabulary is a crucial foundation in English language learning, and Duolingo's potential as an innovative digital learning tool. Using a quantitative quasi-experimental method, we compared two groups of students: one group learned using Duolingo (the experimental group) and the other used traditional methods (the control group). The subjects of this study were all 10th-grade students at SMK Al-Kautsar Sriwijaya for the 2024/2025 academic year. Two classes were specifically selected (purposive sampling) to be the experimental and control groups. To measure vocabulary mastery, both groups were given a pre-test and a post-test. The collected data were then quantitatively analyzed using an independent t-test to determine the difference in average post-test scores between the two groups. The analysis results showed a significant difference in vocabulary mastery between students who used Duolingo and those who did not. The experimental group's average post-test score was significantly higher. This demonstrates that the Duolingo application is effective in improving students' English vocabulary mastery. Therefore, Duolingo can be recommended as an innovative and engaging vocabulary learning tool for use in schools.